The Needs Analysis For Developing A Mobile-Virtual Reality Imagery Training - Yahya Eko Nopiyanto; Bayu Insanistyo; Dian Pujianto; Ipa Sari Kardi; Defliyanto Defliyanto; Ibraheem Musa Oluwatoyin (Universitas Sriwijaya, 2026)
The purpose of this research is to analyze student-athletes' needs for mobile VR-based imagery training so that a design that is adaptive for student-athletes can be produced. The design of this study is quantitative descriptive. Participants in this study were 49 high school student-athletes in Bengkulu City. Data collection was carried out using an instrument in the form of a questionnaire that had validity (0.72) and reliability (0.86). Data were analyzed quantitatively using the percentage technique. Results: 1) Student-athletes have a high need for the development of mobile-VR-based imagery training in terms of training needs (74.17%), technological readiness (69.83%), and material needs (74.27%), 2) The most significant obstacle felt by student-athletes in conducting conventional imagery training is the difficulty in getting a clear picture (41.70%), 3) Student-athletes believe that the development of mobile-VR-based imagery training is essential to do (50%), 4) The content most needed by student-athletes in developing mobile-VR-based imagery training is feedback on performance (50%), 5) the support needed by student-athletes in conducting mobile-VR-based imagery training is content that is tailored to the athlete's needs (52.80%). The findings indicate that student-athletes demonstrate a high level of need for imagery training and technological readiness. Key limitations of conventional imagery training include difficulties in generating clear mental images and lack of interactive engagement. Furthermore, performance feedback and user-centered content emerged as the most critical features for system development.